AB0689 THE IMPORTANCE OF THE SUN. VITAMIN D AND SPONDYLOARTHRITIS: OUR EXPERIENCE IN A THIRD LEVEL HOSPITAL. (13th June 2020) - González Fernández, I.; Álvarez Castro, C.; Moriano, C.; López Robles, A.; Larco Rojas, X. E.; Vallejo Pascual, M. E.
Abstract : Background: Vitamin D plays an important role in the pathogenesis of autoimmune diseases, so that it has been shown that an adequate level is associated with a lower risk of developing this group of entities as well as a lower severity of them. Specifically, in spondyloarthritis (SpA) the deficiency has been associated with greater aggressiveness and greater radiological progression. Objectives: Assess levels of vitamin D in patients diagnosed with SpA in the León University Assistance Complex and study its possible relationship with different clinical-epidemiological variables. Methods: Prospective observational study between January 1, 2019 and December 31, 2019 with consecutive sampling of patients diagnosed with SpA (New York criteria, ASAS) in our hospital between 1973 and 2018. It was taken as a cut-off point for vitamin normality D those values ≥ 30 ng / ml. The disease activity was assessed based on BASDAI and CRP level (taking as a cut-off point 5 mg/l, reference value of our hospital and ruling out elevation due to intercurrent processes) in the last consultation. Positive values above 130 mlg/dL were considered for the orosomucoid and for calprotectin as undetermined values between 50-100 mg/kg feces and suspected IBD greater than 100 mg/kg feces. An attempt was made to link the value of vitamin D with disease activity, tobacco, the development of uveitis and the presence of subclinical intestinal inflammation. Results: 132 patients were included, of which 60.6% were men with a mean age of 49.35 ± 12.95 years. 84.8% were B27 positive. 88.6% met New York criteria. 35.6% suffered uveitis at some time during their evolution. As for tobacco, 68.2% were non-smokers, 12.9% were former smokers and 18.9% were active smokers. 6.8% of the sample presented positivity for the orosomucoid and 37.8% alterations in calprotectin (of which 24.2% were undetermined and 13.6% suspected of inflammatory bowel disease). Only 25% of patients had elevated CRP levels and 11.4% of patients had BASDAI> 4. 50.8% of our sample had optimal levels of Vitamin D while 49.2% were at low values. A statistically significant association was observed between hypovitaminosis D and elevated CRP levels (p 0.038). In our sample we found no statistical association with uveitis or with markers of subclinical inflammatory activity. Conclusion: -Almost half of the patients in our sample have hypovitaminosis D which is probably attributable to the meteorological characteristics of León region. -Low levels of vitamin D are statistically significantly related to higher levels of CRP and, therefore, with greater disease activity. -No significant relationship was found with uveitis or with a higher risk of subclinical intestinal inflammation in our simple. References: [1]Castro Domínguez F, Salman Monte TC, Blanch Rubió J . Vitamin D in rheumatic diseases. Rev Osteoporos Metab Miner. 2017; 9 (1) supplement: 31-39. Disclosure of Interests: None declared